THE INFLUENCE OF THE ENGLISH LEARNING INTEREST TOWARD ENGLISH SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMP 02 PETARUKAN IN 2005/2006 ACADEMIC YEAR - NURJAYANTI , GUSTIN (2006)
This study is intended to describe the student's English learning interest and students speaking ability and to find out whether or not there is a positive and significant correlation between the students' English learning interest and the students' speaking ability. The total population of this research is 271 students of the second year students of SMPN 02 Petarukan in 2005/2006 academic year while the number of sample is 50. In taking the sample, the writer uses the random sampling technique. The document is employed to reveal the students speaking ability while the questionnaire is used to take the data of the students' English learning interest. The writer applies Product-moment correlation to measure the validity of the instrument and reliability of the instrument. Data analysis is calculated by using descriptive and inferential statistics. The inferential statistics consists of the normality test, the linearity test and hypothesis test. The result of the analysis shows that the mean of the indepen dent variable (the students English learning interest) is 107, 62 and standard deviation is 11, 13. The students' English learning interest is categorized into good category. Meanwhile, the mean of the dependent variable (the students speaking ability) is 7, 56 and standard deviation is 0,907. The students speaking ability is in good category. The inferential analysis yields the correlation coefficient of the independent and dependent variable is 0,432. This value is higher than r table at N 50, that is, 0,279. It means that there is a positive and significant correlation between the students' English learning interest and the students speaking ability. The effective contribution of the independent variable to the dependent one is 30%.